Defect detection in glass fabric reinforced thermoplastics by laboratory-based X-ray scattering. (1st March 2023) - Öztürk, Özgul; Brönnimann, Rolf; Modregger, Peter
Abstract: Glass fabric reinforced thermoplastic (GFRT) constitutes a class of composite materials that are especially suited for automobile construction due to their combination of low weight, ease of production and mechanical properties. However, in the manufacturing process, during forming of prefabricated laminates, defects in the glass fabric as well as in the polymer matrix can occur, which may compromise the safety or the lifetime of components. Thus, the detection of defects in GFRTs for production monitoring and a deep understanding of defect formation/evolution is essential for mass production. Here, we experimentally demonstrate that local fiber shifts in the fabric, a type of defect difficult to image with other techniques, can be detected reliably by X-ray scattering based on the edge-illumination principle. This implies applications for research on mechanism of defect formation as well as for industrial application in production monitoring. Highlights: X-ray transmission and scattering signals are anti-correlated for GFRT samples. Local fiber shifts defects in GFRT can be detected by X-ray transmission and scattering. Defects are detectable in the hidden glass fiber layer.